Seed and vegetation dynamics in undamaged and degraded coastal habitats of the Hudson Bay lowlands. - Chang, Esther R. (Ottawa : National Library of Canada = Bibliotheque nationale du Canada, 2000)
Grubbing and grazing by increasing numbers of lesser snow geese (Anser caerulescens caerulescens) have led to loss of vegetation and soil degradation in salt marshes and on beach ridges. These changes have had a deleterious effect on the soil seed bank by reducing density of seeds and shifting the composition from species present prior to the disturbance to invasive species. In the salt marsh, more recently degraded plots had greater revegetation potential from the remaining seed bank than plots where loss of vegetation was of long standing. Seed banks in beach-ridge soils were less affected by degradation due to the greater proportion of weedy species present in the original vegetation. Studies of the seed and vegetation dynamics in the supratidal marsh indicated that while there were no systematic differences between the seed rain in undamaged and degraded sites, degradation processes constrain recruitment at the entrapment, germination and establishment stages.